Efficiency-optimal iso-planar tool path generation for five-axis finishing machining of freeform surfaces. (February 2017) - Hu, Pengcheng; Chen, Lufeng; Tang, Kai
Abstract: Traditional works in five-axis iso-planar tool path generation mainly aim at finding the best direction of the parallel drive planes so that the total length of the tool path is minimized. However, an iso-planar tool path optimized this way is often found to be inferior in improving the machining efficiency, as it ignores the kinematic constraints of the specific machine tool. In this paper, we present an efficiency-optimal iso-planar tool path generation algorithm for multi-axis machining of freeform surfaces that takes the kinematic capacities of the machine tool in full consideration. Rather than trying to maximizing the cutting strip width alone, the proposed algorithm aims at globally maximizing the material removal rate which considers both the cutting strip width and the machine's kinematic capacities and hence is a more comprehensive reflection of machining efficiency. In addition, we further enhance the machining efficiency by automatically adjusting the tool orientation along the tool path. Both computer simulation and physical machining experimental results show that, when compared with the traditional iso-planar tool path generation algorithms, the proposed method is often able to substantially improve the machining efficiency. Highlights: A scalar field EMRR* is proposed to represent the machining efficiency. The machine's kinematic constraints are reflected in the proposed EMRR*. Efficiency-optimal iso-planar tool path is generated based on EMRR*. B-spline based tool orientation optimization method is proposed. Effectiveness of the proposed methods is tested from experiments.